Penjualan Es Kul Kul Di Kawasan UINSU Guna Membangun Jiwa Kewirausahaan Dalam Mahasiswa - Adelia Putri; Annisa Annisa; Depi Yanti (Pusat Riset dan Inovasi Nasional, 2025)
Frozen banana ice, or what used to be called ice kul kul, is actually not a new product. This type of dessert has actually been known for a long time, but because its shape is too simple, it is not very popular. Developing an entrepreneurial spirit in students is one way or alternative to overcome the problem of unemployment in Indonesia. That's why undergraduate graduates are directed and guided so that they don't just think about becoming a job seeker. This research is descriptive qualitative research. Data sources consist of primary data and secondary data. Primary data comes from student practice and observation. students can develop students because entrepreneurship can benefit themselves and others. This course requires students to practice directly in practice, so that it can build an entrepreneurial spirit in students. So from these activities they can gain a lot of experience on how to do business properly and correctly. Market their products in a way that makes them known to many consumers, without violating ethics.